Effect of introducing RC infill on seismic performance of damaged RC frames - Ersoy, Uğur; Özcebe, Güney; TÜRK, AHMET MURAT (TECHNO-PRESS, PO BOX 33, YUSEONG, DAEJEON 305-600, SOUTH KOREA, 2006)
The main objective of this study was to investigate the seismic behavior of damaged reinforced concrete frames rehabilitated by introducing cast in place reinforced concrete infills. Four bare and five infilled frames were constructed and tested. Each specimen consisted of two (twin) 1/3-scale, one-bay and two-story reinforced concrete frames. Test specimens were tested under reversed-cyclic lateral loading until considerable damage occurred. RC infills were then introduced to the damaged specimens. One bare specimen was infilled without being subjected to any damage. All infilled frames were then tested under reversed-cyclic lateral loading until failure. While some of the test frames were detailed properly according to the current Turkish seismic code, others were built with the common deficiencies observed in existing residential buildings. The variables investigated were the effects of the damage level and deficiencies in the bare frame on the seismic behavior of the infilled frame. The deficiencies in the frame were; low concrete strength, inadequate confinement at member ends, 90 degree hooks in column and beam ties and inadequate length of lapped splices in column longitudinal bars made above the floor levels. Test results revealed that both the lateral strength and lateral stiffness increased significantly with the introduction of reinforced concrete infills even when the frame had the deficiencies mentioned above. The deficiency which affected the behavior of infilled frames most adversely was the presence of lap splices in column longitudinal reinforcement.
Keywords: reinforced concrete; infill; building frames; cyclic test; strength; stifffiess; rehabilitation; betonarme; dolgu; bina çerçeveleri; döngüsel test; kuvvet; rehabilitasyon